A sensitive scoring system for the longitudinal clinical evaluation and prediction of lethal disease outcomes in newborn mice - Fehlhaber, Beate; Heinemann, Anna S.; Ruebensam, Kathrin; Willers, Maike; Voellger, Lena; Pfeifer, Sandra; Von Koeckritz-Blickwede, Maren; Viemann, Dorothee (Scientific Reports, 2019)
Neonatal animal models are increasingly employed in order to unravel age-specific disease mechanisms. Appropriate tools objectifying the clinical condition of murine neonates are lacking. In this study, we tested a scoring system specifically designed for newborn mice that relies on clinical observation and examination. Both, in a neonatal sepsis model and an endotoxic shock model, the scoring results strongly correlated with disease-induced death rates. Full as well as observation-restricted scoring, reliably predicted fatality and the remaining time until death. Clinical scores even proved as more sensitive biomarker than 6 traditionally used plasma cytokine levels in detecting sepsis at an early disease stage. In conclusion, we propose a simple scoring system that detects health impairments of newborn mice in a non-invasive longitudinal and highly sensitive manner. Its usage will help to meet animal welfare requirements and might improve the understanding of neonatal disease mechanisms.
CRIS-Team Scopus Importer:2023-03-23